The Salon as an Arena of Secularization. Music performed on Intimate Stages in the last decades of the 18 century. New perspectives on the function of the Salons (Theatrum historiae, 2009)
This article demonstrates how the salons in Copenhagen in the last decades of the 18 century might be seen as an arena of secularization. These environments are stages for the performance of Johann Christoph Friedrich Bachs Geistliche Lieder. The texts of Geistliche Lieder are religious, and written by the vicar in St. Petri congregation in Copenhagen. Bach breaks with the prevailing norm for such songs, and by doing so, he creates tension between the traditional religiosity of the text and the novel secularization of the setting.
Keywords: secularization; Copenhagen; salons; Johann Christoph Friedrich Bach; Sturm und Drang